Industrial training e-logbook system - Tracey Chia Ai, Quin (2013)
Industrial Training is the process of undertaking an internship at a company related to one’s field of study. There are thousands of university students undergoing internship every semester. As there are a large number of records to manage process, Industrial Training e-Logbook System (ITeLS) is developed to ease the workload. The development process of ITeLS is partitioned into phases such as planning, analysis, design, implementation and testing, based on the Rapid Application Development (RAD) methodology. By implementing ITeLS, the internship records were able to be dynamically updated and accessed by all parties at any time. For future enhancements, a mobile version may be developed for increased mobility and ease of access.